Modeling the Resilient Modulus Variation of In Situ Soils due to Seasonal Moisture Content Variations - Kevin Gaspard; Zhongjie Zhang; Gavin Gautreau; Khalil Hanifa; Claudia E. Zapata; Murad Abufarsakh (Advances in Civil Engineering)
LTRC is conducting a research project to determine the seasonal variation of subgrade resilient modulus (MR) in an effort to implement PavementME. One objective of that project, which is presented in this paper, was to locally calibrate the Enhanced Integrated Climate Model’s (EICM Fenv) curve for seasonal subgrade MR changes. Shelby tube sampling was conducted on six different roadways to a depth of approximately 7.92 m beneath the shoulder pavement’s base course. The AASHTO T-99 MR test method was used on all samples with an additional eight specimens being tested with NCHRP 1–28A MR test method. Four soils from Louisiana which were not from the six roadways were also tested and included in the analyses. Once the MR tests were completed and plotted, it was noticed that there was a rather large scatter (R2 = −0.266) around the EICM Fenv curve. The authors hypothesized that this occurred due to the density differences between in situ and remolded specimens. Further analyses confirmed this hypothesis. LTRC developed a new method based on the EICM Fenv method to determine the relationship between changes in subgrade MR as a function of changes in moisture content with the in situ moisture content and MR used as the control. This method differs from the EICM Fenv in that the EICM Fenv uses optimum moisture content as the controlling parameter. The LTRC method can be used for design purposes as well as level 2 inputs into the EICM.